In vitro cytotoxic effects of Smilax aspera L. roots on cancer cell lines - Dalkilic, Semih; Korkmaz, Ismail; Dalkilic, Lutfiye Kadioglu; Akay, Gokhan; Fidan, Songul (Elsevier, 2022)
Approximately, 14 million cancer cases are seen annually, and cancer accounts for 20% of all deaths in the world. However, the incidence of cancer is increasing every year. The fact that the survival rate in cancer is not at the desired level makes cancer a pathology with a high mortality rate. Scientists conduct intensive research on strategic issues such as new diagnostic methods, identification of new candidate drug molecules, and detection of molecules or molecular pathways that may be targeted for new drugs. In this study; The cytotoxic activity and apoptotic mechanism were investigated root extracts of Smilax aspera L., whose roots are edible. This study, cytotoxicity of S. aspera root extracts on MDA-MB-231, A549 and OVCAR3 cell lines by MTT method and apoptotic activity on OVCAR3 cell line by double staining and gene expression levels were determined for the first time. As a result of the study, S. aspera root extracts showed a significant cytotoxic effect on three cell lines at different rates. In addition, it suppressed the BCL2 gene, which has an important role in the prevention of apoptosis, and it was determined to have an apoptosis-inducing effect. In this respect, it is seen that S. aspera is a strategically important plant that can be used in cancer treatment.
Keywords: Apoptosis; Cytotoxicity; Gene expression; Smilax aspera